Anti-seizure Medication Prescription in Adult Outpatients With Epilepsy in China, 2013–2018 - Yu, Lingyan; Zhu, Wenjie; Zhu, Xiuping; Lu, Yan; Yu, Zhenwei; Dai, Haibin (Frontiers in Neurology, 2021)
This study aimed to assess the national trends in ASM prescribing in Chinese adult outpatients with epilepsy over a 6-year period from 2013 to 2018. Prescriptions for adult outpatients with epilepsy from hospitals in six major cities were extracted from the database of the Hospital Prescription Analysis Cooperative Project. Trends in the annual prescriptions and expenditure of ASM were analyzed. Prescribing patterns (monotherapy or combination therapy) were also assessed. A total of 225,767 prescriptions from 60 hospitals were eligible and extracted for analysis. The number of ASM prescriptions increased from 28,360 in 2013 to 44,110 in 2018, and the corresponding cost increased from 9,452,990 Chinese Yuan (CNY) in 2013 to 14,627,865 CNY in 2018. The share of newer ASM use increased continuously, accounting for 56.75% of prescriptions and 85.03% of expenditure in 2018. The most frequently prescribed ASMs were sodium valproate and levetiracetam. The proportion of sodium valproate use decreased, while the proportion of levetiracetam use increased dramatically both in terms of ASM prescriptions and expenditure. Monotherapy was more frequent than combination therapy. The three most common combination therapies were sodium valproate/lamotrigine, levetiracetam/oxcarbazepine, and sodium valproate/levetiracetam. In summary, ASM use increased rapidly in terms of the number of ASM prescriptions and cost during the 6-year period, which raises concern regarding the rational use and pharma-economic profiles of ASMs. In place of valproate, levetiracetam became the most frequently used ASM. The development of ASM prescribing is in line with therapy guidelines and reflects the current state of research in China.